Distribution , Ecology and Population Structure of Euphorbia monchiquensis , an Endemism in Southern Portugal - Fox, Xenia; Deil, Ulrich (Silva Lusitana, 2004)
Euphorbia monchiquensis is, within the widespread and euryoecious E. paniculata- complex, an acidophilous subspecies, endemic in Southern Portugal. To evaluate the vulnerability of this taxon vis-a-vis disturbance and landuse changes, we studied the actual distribution, the population size, the ecological requirements and the coenological value of this taxon in the Serra de Monchique, a mountainous region in the Algarve Hinterland. Data sampling was between April and July 2001. The quite constant branching system of this half shrubby spurge allows to determine the age of the indivuduals from the plant architecture and therefore to study the demographic structure in a non-destructive way. 1618 individuals, clustered in 46 populations, have been registered in the Serra. 88% were in flower. Euphorbia monchiquensis is rare relative to its overall distribution. It shows a bimodal altitudinal and coenological pattern. The majority of the populations are concentrated in the most humid mid altitudes and on the luv-ward northwestern side of the Serra. A few populations occur in the dry lowlands, linked to riverine shrublets. The plant depends on a good water supply but does not need shadowing. Within its limited bioclimatic niche, the spurge has a certain capacity of recolonisation and is not extremely sensitive to disturbance. Humid forests of the Euphorbio monchiquensis-Quercetum canariensis are just one of the preferred sociological situations. The coenological spectrum includes pure cork oak forests, Castanea sativa coppices, Eucalyptus-afforestations, mantle communities (Lonicero-Rubetum, Rubo- Nerietum), Origanion virentis fringes, abandoned meadows and roadside verges. It was in this kind of secondary habitats with intermittent disturbance, that most of the juvenile plants could be stated. Only very few plantlings were found. Most of the recorded populations are well balanced in their medium age classes, others are overaged. A correlation between habitat qualities, the reproductive effort and the regeneration efficiency could not be found. Four inflorescence- -morphotypes can be distinguished. The inflorescence architecture becomes more complex with increasing age. Euphorbia monchiquensis is not an extremely endangered, but a vulnerable species. It can be threatened by the process of Eucalyptus afforestation and by the spontaneous spread of Acacia dealbata. To give a reliable answer to the extinction risk, further aspects of its life cycle, seed bank characteristics, and reproductive behaviour have to be studied.
Keywords: age-states; conservation biology; landuse; plant architecture; reproduction; serra de monchique

Distribution , Ecology and Population Structure of Euphorbia monchiquensis , an Endemism in Southern Portugal - Fox, Xenia; Deil, Ulrich (Silva Lusitana, 2004)
Euphorbia monchiquensis is, within the widespread and euryoecious E. paniculata- complex, an acidophilous subspecies, endemic in Southern Portugal. To evaluate the vulnerability of this taxon vis-a-vis disturbance and landuse changes, we studied the actual distribution, the population size, the ecological requirements and the coenological value of this taxon in the Serra de Monchique, a mountainous region in the Algarve Hinterland. Data sampling was between April and July 2001. The quite constant branching system of this half shrubby spurge allows to determine the age of the indivuduals from the plant architecture and therefore to study the demographic structure in a non-destructive way. 1618 individuals, clustered in 46 populations, have been registered in the Serra. 88% were in flower. Euphorbia monchiquensis is rare relative to its overall distribution. It shows a bimodal altitudinal and coenological pattern. The majority of the populations are concentrated in the most humid mid altitudes and on the luv-ward northwestern side of the Serra. A few populations occur in the dry lowlands, linked to riverine shrublets. The plant depends on a good water supply but does not need shadowing. Within its limited bioclimatic niche, the spurge has a certain capacity of recolonisation and is not extremely sensitive to disturbance. Humid forests of the Euphorbio monchiquensis-Quercetum canariensis are just one of the preferred sociological situations. The coenological spectrum includes pure cork oak forests, Castanea sativa coppices, Eucalyptus-afforestations, mantle communities (Lonicero-Rubetum, Rubo- Nerietum), Origanion virentis fringes, abandoned meadows and roadside verges. It was in this kind of secondary habitats with intermittent disturbance, that most of the juvenile plants could be stated. Only very few plantlings were found. Most of the recorded populations are well balanced in their medium age classes, others are overaged. A correlation between habitat qualities, the reproductive effort and the regeneration efficiency could not be found. Four inflorescence- -morphotypes can be distinguished. The inflorescence architecture becomes more complex with increasing age. Euphorbia monchiquensis is not an extremely endangered, but a vulnerable species. It can be threatened by the process of Eucalyptus afforestation and by the spontaneous spread of Acacia dealbata. To give a reliable answer to the extinction risk, further aspects of its life cycle, seed bank characteristics, and reproductive behaviour have to be studied.
Keywords: age-states; conservation biology; landuse; plant architecture; reproduction; serra de monchique

Farming practices and Roller Coracias garrulus conservation in south-west Spain - Aviles, J M; Parejo, D (BIRD CONSERVATION INTERNATIONAL, 2004)
There are no previous studies supporting the link between the decline of Roller Coracias garrulus populations in the Palaearctic and agricultural intensification. We studied the effect of farming practices on Roller reproduction during 1988-1991 in south-west Spain. Nest-boxes were installed on power pylons that crossed six different man-made habitats representing the most characteristic habitats in the Mediterranean region: pasture fields with and without holm oak Quercus roffindifolia trees, cereal fields with and without holm oak trees, scrub fields and irrigated fields. Rollers nesting in nest-boxes erected in unwooded pasture field had the highest breeding success, suggesting that this is the most suitable nesting habitat of Rollers in the region. There were no significant effects of farming practices in habitat adjacent to nests on Roller laying date and clutch size. However, after controlling for laying date, current agricultural practices around nests affected chick mortality, with higher losses in irrigated fields. Breeding success and egg productivity were also affected by farming activities, with the lowest values in irrigated fields. Future conservation plans for Rollers should consider that nest-box provision might increase habitat suitability for Roller reproduction and that highly intensified agricultural practices might have deleterious effects on Roller populations.
APS
Keywords: Agricultural intensification; farming practices; Mediterranean; nest-boxes; reproduction; Roller Coracias garrulus

Farming practices and Roller Coracias garrulus conservation in south-west Spain - Aviles, J. M.; Parejo, D. (BIRD CONSERVATION INTERNATIONAL, 2004)
There are no previous studies supporting the link between the decline of Roller Coracias garrulus populations in the Palaearctic and agricultural intensification. We studied the effect of farming practices on Roller reproduction during 1988-1991 in south-west Spain. Nest-boxes were installed on power pylons that crossed six different man-made habitats representing the most characteristic habitats in the Mediterranean region: pasture fields with and without holm oak Quercus roffindifolia trees, cereal fields with and without holm oak trees, scrub fields and irrigated fields. Rollers nesting in nest-boxes erected in unwooded pasture field had the highest breeding success, suggesting that this is the most suitable nesting habitat of Rollers in the region. There were no significant effects of farming practices in habitat adjacent to nests on Roller laying date and clutch size. However, after controlling for laying date, current agricultural practices around nests affected chick mortality, with higher losses in irrigated fields. Breeding success and egg productivity were also affected by farming activities, with the lowest values in irrigated fields. Future conservation plans for Rollers should consider that nest-box provision might increase habitat suitability for Roller reproduction and that highly intensified agricultural practices might have deleterious effects on Roller populations.
APSAPSThe following values have no corresponding Zotero field: pub-location: 40 WEST 20TH ST, NEW YORK, NY 10011-4211 USA publisher: CAMBRIDGE UNIV PRESS
Keywords: Agricultural intensification; farming practices; Mediterranean; nest-boxes; reproduction; Roller Coracias garrulus

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC; Blondel, Jacques; Thomas, DonaldW (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM.; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC.; Blondel, Jacques; Thomas, DonaldW. (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

Fenofases florales en quercus rotundifolia lam. - Vázquez, F M (II Congreso Forestal Español, 1997)
In this work the floral stages are introduced that it is happened in the masculine and feminine flowering of the holm-oak (Quercus rotundifolia Lam.). In each described stages they incorporate data on the floral morphology: state of development that it reach the catkins, the floral group and the tlowers. Also data of the receptive state in the are inserted feminine tlowers and ripening and viability grade of the grain of ponen and ovule. Finally is represented in a graphic each one of the described stage. K.W.:
Keywords: flowering; holm-oak; Ovule; pollen; Quercus rotundifolia; reproduction; Stages